2013
DOI: 10.4253/wjge.v5.i2.39
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing quality of bowel preparation for colonoscopy

Abstract: Recent technological advances in colonoscopy have led to improvements in both image enhancement and procedural performance. However, the utility of these technological advancements remain dependent on the quality of bowel preparation during colonoscopy. Poor bowel preparation has been shown to be associated with lower quality indicators of colonoscopy performance, such as reduced cecal intubation rates, increased patient discomfort and lower adenoma detection. The most popular bowel preparation regimes current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 75 publications
(96 reference statements)
3
54
0
9
Order By: Relevance
“…[16][17][18] Suspected reasons are reduced colon transit time or comorbidities in elderly patients. 19 A complex administration method is a barrier and could be the reason for poor adherence to the instruction of taking preparation agents in elderly patients. Detailed instructions and counseling could promote successful bowel cleansing.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Suspected reasons are reduced colon transit time or comorbidities in elderly patients. 19 A complex administration method is a barrier and could be the reason for poor adherence to the instruction of taking preparation agents in elderly patients. Detailed instructions and counseling could promote successful bowel cleansing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients using PMC received both sachets on the day before colonoscopy. It has been shown that timing has major influence on the quality of bowel preparation . Moreover, PEG given as a split dose seems to be more effective than a before day‐only administration .…”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients are more likely to have inadequate bowel preparation, thus reducing mucosal visualization and detection of polyps and early CRC. 22,23 Female patients are more likely to have had previous abdominal and pelvic surgery, which may increase the technical difficulty of colonoscopy and impair patient tolerance, reducing the cecal intubation rate. 24 In addition to factors that have an adverse effect on the cecal intubation rate, right side of the colon CRCs are more likely to arise from flat, non-polypoid adenomatous lesions 20,25 that are more difficult to detect with poor bowel preparation.…”
Section: Pccrc Rates Over Timementioning
confidence: 99%